The relationships between the dark triad, anomia, and negative affectivity with Counterproductive Work Behaviours (CWBs) among municipal council employees in Selangor: The moderating effects of locus of control and job grades / Azwan Shah Aminuddin - Aminuddin, Azwan Shah (2023)
Despite the fact that some researchers have gained notoriety by employing certain approaches and focusing on particular Counterproductive Work Behaviours (CWBs), the study focused on the differences discovered in individual personalities that motivate people to engage in CWBs. Locus of Control (LoC) and job grades were also investigated to determine their impacts on the existing link between individual differences and work-related behaviours in order to have a better understanding of how CWBs and individual differences are connected to one another; hence, three main hypotheses were developed for this study. The Dark Triad, which consists of Machiavellianism, Narcissism, and Psychopathy, together with Anomia and Negative Affectivity were the independent variables in this study. Meanwhile, Locus of Control, which is categorised into External (LoC-E) and Internal (LoC-I), as well as job grades (Grades 1, 2, and 3) were employed as the moderating variables. Finally, CWBs that consist of Types S, O, and D misbehaviours were treated as the dependent variable. The stratified quota sampling technique involving 588 respondents was used and their responses were collected via online questionnaires. The findings of this study revealed that the above-mentioned variables exhibited significant relationships with one another. Hierarchical Regression Analysis was conducted and LoC-I was found to moderate the relationships between Narcissism, Psychopathy, and Anomia with Type D CWB as well as psychopathy with Type O CWB, while LoC-E moderated the relationships between Psychopathy and Anomia with Type D CWB. In addition, only Category 2 job grade was found to significantly moderate the relationships between Narcissism and Anomia with Type O CWB and anomia with Type D CWB. The findings of this study should help other scholars to conduct research in this field using other factors and comprehend the topic of Counterproductive Work Behaviours (CWBs) more thoroughly. It is recommended that further investigation needs to explore the influence of other job factors such as reward programmes or job characteristics.